Generation of the induced pluripotent stem cell line UHOMi002-A from peripheral blood mononuclear cells of a healthy male donor - Mathieu Fieldes; Engi Ahmed; Chloé Bourguignon; Joffrey Mianné; Mélanie Martin; Cécile Arnould; Isabelle Vachier; Said Assou; John De Vos; Arnaud Bourdin (Stem Cell Research, 2020)
Human pluripotent stem cells (hiPSC) are highly valuable tools to model lung development and chronic bronchial diseases. We generated a hiPSC line from a highly characterized 40-year-old healthy male nonsmoking donor. Peripheral blood mononuclear cells (PBMCs) were reprogrammed using integration-free Sendai Virus. The cell line had normal karyotype, expressed pluripotency hallmarks, and differentiated into the three primary germ layers.The reported UHOMi002-A iPSC line may be used as a control to model lung development, study human chronic bronchial diseases and drug testing.